Neutron Capture Radiography: Neutron Capture Radiography:a technique for isotopic labelling and analytical imaging with a few stable isotopes - Michel Thellier; Camille Ripoll (The Scientific World Journal)
NCR (neutron capture radiography) may be used successfully for the imaging of one of the stable isotopes of a few chemical elements (especially 6Li and 10B, possibly also 14N, 17O, and others) and for labelling experiments using these stable isotopes. Other physical techniques compete with NCR. However, NCR can remain extremely useful in a certain number of cases, because it is usually more easily done and is less expensive than the other techniques.